Effect of Soret on Unsteady MHD Casson Fluid Flow over a Vertical Surface using Laplace Transformation - S. Dinesh; S. Laxmi Priya (Utilitas Mathematica, 2025)
The unsteady magnetohydrodynamic (MHD) flow of a Casson fluid along an infinite vertical surface that is exponentially stretching is studied analytically in this paper, taking into account the Soret effect. By taking into account the Soret effect, the study expands on current approaches that use the Laplace transform to unravel the flow model's governing equations. A series of coupled partial derivative equations addressing the momentum, energy, and concentration distributions characterize the system's behaviour. The model incorporates a chemical reaction parameter, magnetic field effects, and Casson fluid properties into the equations. The Laplace transform technique is adopted to derive a solution. The study emphasizes how velocity, temperature, and concentration profiles are altered by changes in the chemical reaction parameter. Furthermore, the consequence of variables like magnetic field strength M, Casson fluid parameter β, Grashof number Gr, Prandtl number Pr, thermal radiation Rd, Schmidt number Sc, and Prandtl number Pr are all carefully investigated. The results contribute to a better understanding of MHD flows in Casson fluids and their significance in heat and mass transfer systems by providing insightful information for improving industrial processes involving the interaction of magnetic fields and non-Newtonian fluids under the dominance of the Soret effect.